BILIMLENDIRIW MÁKEMELERIN BASQARÍW PROCESINIŃ PEDAGOGIKALÍQ HÁM PSIXOLOGIYALÍQ ÓZGESHELIKLERI - Qadirov, Q.; Mambetnazarov, R. (SCIENCE and SOCIETY, 2022)
The article deals with the main approaches and methods of assessing the management effectiveness of the educational institution. An assessment of the effectiveness of the management process has been carried out based on the results of the manager’s practical works. Also, in the article, important issues of the factors that should be taken into consideration the implementation of management have been described. Furthermore, theoretical views on the effectiveness of management activities in education have been analyzed in the paper.